Corporate motives for public shares offering during the financial crisis - Mihaela Grubisic Seba; Silvije Orsag (UTMS Journal of Economics, 2015)
Despite greater constraints for obtaining bank loans, public shares' offerings ceased in the SEE region since the onset of the financial crisis in 2008. With scarce IPOs and SEOs as well as debt offerings, Croatian capital market stands as prime example of mandatory shares' listing rule application. Surveys of CFOs on going-public vs staying-private decisions are rare even in developed countries and are mostly conducted during the hot IPO markets. In this paper the motives of shares' issuance are compared between publicly- and privately-held companies during the financial crisis. Research results showed that companies would not issue shares to the public to raise funds for their investments and growth.
Keywords: G30; G38; N24; O16; 330; shares; initial public offering; CFOs' survey; capital market; financial crisis; Croatia